Risk assessment using Business Intelligence framework for organizations: A Systematic Literature Review - Esiefarienrhe, Bukohwo Michael; Khutswane, Thoriso (The Indonesian Journal of Computer Science, 2023)
Today many organizations are facing different kinds of risks as they are migrating towards new technologies. Risk assessment is one of the methods that were developed to help with identifying, assessing, and managing risks. Several studies have been conducted regarding risk assessment and business intelligence, however few studies have been conducted on how both can be integrated and use. A systematic literature review is conducted to understand the importance of risk assessment and business intelligence for organizations. Due to the relevance of BIS and the need for risk analysis before development and implementation, there is need to critically examine literaure to understand what has been done and the gap that exist for future researchers to implement. Therefore this study use the Systematic Literature Review methodology to collect 125 academic publications from over 6 academic, business and research databases for review. Inclusion and exclusion criteria were applied to the papers proning them to 65 and when quality assessment were applied, the total paper obtained amounted to 25 which were eventually used for the review. The results obtained from the review study showed that although there are much publication related to business intelligence and risk assessment, most of them did not incorporate quality assessment, rigorous testing, creation of new analytical tools, application of AI, and deep learning algorithms into developing their business intelligence systems. Future research focus areas resulting from this study were also highlighted in the conclusion session of this study.